Performance of Pantaneira Breed Cows on Pasture Supplemented with Homeopathic Additives and Yeast - Florentino, Leandra da Silva; Silva, Evellyn Richelly Ferreira da; Santos, Mariana; Torgan, Daniele Portela de Oliveira; Júnior, Fernando Miranda de Vargas; Luz, Dirce Ferreira; Oliveira, Dalton Mendes de; Oliveira, Marcus Vinicius Morais de (Homeopathy, 2025)
To improve the nutritional efficiency of ruminants and promote well-being in a natural and effective manner, the use of additives such as homeopathic products and yeast has been increasingly incorporated into diets, especially in grazing systems.To evaluate the effects of homeopathic products and yeast on the performance of Pantaneira cows maintained in rotational grazing on Mombaça grass in the Pantanal, Brazil.Sixty cows were assigned to a completely randomized design with four treatments and 15 replicates. The treatments were: CTL: control (without additives); HOM: homeopathic (4 g/kg Entero 100, 4 g/kg Figotonus, and 4 g/kg Convert H); YEA: yeast (24 g/kg Saccharomyces cerevisiae); and HY: homeopathic + yeast (4 g/kg Entero 100, 4 g/kg Figotonus, 4 g/kg Convert H + 24 g/kg S. cerevisiae). The variables measured included forage and supplement intake, diet digestibility, weight gain, and feed conversion. Data were subjected to analysis of variance (ANOVA), followed by Tukey and Duncan tests, with a significance level set at 5%.Cows in the HY treatment group showed higher average daily gains and better feed conversion compared to the CTL treatment (p ≤ 0.05). They exhibited higher digestibility of dry matter, crude protein, neutral detergent fiber, acid detergent fiber, and ether extract, as well as higher levels of total digestible nutrients and digestible energy (p ≤ 0.05).The inclusion of 4 g/kg Entero 100, 4 g/kg Figotonus, 4 g/kg Convert H, and 24 g/kg S. cerevisiae improved nutrient digestibility, body weight gain and feed conversion in Pantaneira cows.
Keywords: cattle; feed conversion; grazing; natural additive; Saccharomyces cerevisiae